2021
DOI: 10.1111/psyp.13785
|View full text |Cite
|
Sign up to set email alerts
|

Realistic (3D) looming of emotional visual stimuli: Attentional effects at neural and behavioral levels

Abstract: Previous research shows that endogenous attention (the controlled selection of certain aspects of our environment) is enhanced toward emotional stimuli due to its biological relevance. Although looming affective stimuli such as threat seem even more critical for survival, little is known about their effect on endogenous attention. Here, we recorded neural (event‐related potentials, ERPs) and behavioral responses (errors and reaction times) to explore the combined effect of emotion and looming motion. 3D‐recrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 100 publications
(130 reference statements)
1
2
0
Order By: Relevance
“…This contradicts the findings of larger P1 amplitudes for looming angry faces 28 . Although it also has been reported for later ERPs (e.g., for looming threat-related animals 62 ), looming might enhance earlier emotion-sensitive ERPs, especially www.nature.com/scientificreports/ those elicited by faces, and prove more effective than the static images used in the present study. Similarly, enhanced emotion effects on later ERPs have been shown for dynamic facial expressions 63 .…”
Section: Discussionsupporting
confidence: 41%
“…This contradicts the findings of larger P1 amplitudes for looming angry faces 28 . Although it also has been reported for later ERPs (e.g., for looming threat-related animals 62 ), looming might enhance earlier emotion-sensitive ERPs, especially www.nature.com/scientificreports/ those elicited by faces, and prove more effective than the static images used in the present study. Similarly, enhanced emotion effects on later ERPs have been shown for dynamic facial expressions 63 .…”
Section: Discussionsupporting
confidence: 41%
“…This contradicts the findings of larger P1 amplitudes for looming angry faces 28 . Although it also has been reported for later ERPs (e.g., for looming threat-related animals 62 ), looming might enhance earlier emotion-sensitive ERPs, especially those elicited by faces, and prove more effective than the static images used in the present study. Similarly, enhanced emotion effects on later ERPs have been shown for dynamic facial expressions 63 .…”
Section: Discussionsupporting
confidence: 39%
“…Regarding the latter, the LPC component has been linked to endogenous rather than exogenous attention (e.g., see the reviews by Carretié 2014 ; MacNamara et al 2012 and later works by Carboni et al 2017 ; López-Martín et al 2013 ). Indeed, the emotional content of pictures has been reported to enhance the amplitude of this component (for a review, see Olofsson et al 2008 , and later works by Feng et al 2014 ; Fernández‐Folgueiras et al 2021 ; Nordström and Wiens 2012 ). In our study, the LPC showed maximal amplitudes to dynamic negative distractors, but also static negative, in both cases differing from positive (but not from neutral, in the latter case).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, LPC amplitudes have been shown to be sensitive to the proximity of stimulation, showing greater amplitudes for closer than for farther stimuli (Valdés-Conroy et al 2014 ). Behavioral data have also shown improved task performance (lower reaction times and/or errors) when emotional content is endogenously attended (Del Zotto and Pegna 2015 ; Fernández‐Folgueiras et al 2021 ; Yuan et al 2014 ). Our results corroborate previous literature as threatening stimuli were associated with the highest accuracy in the line orientation task.…”
Section: Discussionmentioning
confidence: 99%